Valuation of plantations to stabilize livelihoods for highlands of Kon Ha Nung, Gia Lai province based on remote sensing and GIS technology - Huu Viet Nguyen Hieu; Ngoc Nguyen Thach; Van Pham Manh; Thi Dang Ngoc; Cao Nguyen Tung; Anh Le Hung; Ba Dinh Duy; Trung Ngo Dung (E3S Web of Conferences)
In Vietnam, forests provide many economic benefits, contributing to stabilizing livelihoods for people living in mountainous areas. Forest pricing policies provide excellent opportunities for the forestry industry to help society and stakeholders correctly and sufficiently identify the value of forests. This study employed a combination of Sentinel-2 multispectral optical remote sensing technology and field surveys to value the forests in the Kon Ha Nung Plateau area. The results yielded a high- accuracy map of the current forest status in the study area, with an overall accuracy of 86.11% and a kappa of 0.849, which served as the basis for determining the planted forest area. This map encompassed 3,692.4 hectares and featured 11 forest tree species, planted in two main forms: single species and combined. We selected a pilot to assess the value of plantations for two major tree species in the area: Acacia and Eucalyptus. In conjunction with local forestry development policy frameworks, the results of field surveys help determine the economic sources of forests through the payment of forest environmental services and forest protection assignments. The research results can aid in evaluating the effectiveness of activities related to local forest management policies and stabilizing livelihoods for local people.